Potencial de uso agrícola de levedura seca inativa de cana-de-açúcar e de resíduos orgânicos - Braga, Marilena de Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The use of organic waste as fertilizer may cause improvement in chemical and physical soil properties, as these residues have significant amounts of nutrients, especially N, and high organic carbon content. In general, the availability of these C residues to the ground is smaller as compared with synthetic fertilizers, because of the way that N is connected to these fertilizers. Therefore, there is the necessity studies in order to estimate the mineralization of N and the time these reactions occur, assisting a suitable recommendation of this waste as fertilizer. Thus, the aim of this work was to evaluate (I) under laboratory conditions, inactive dry yeast mineralization of sugarcane (ULCI), chicken manure (EG), cattle manure in corral confinement (EB) and biosolids (BS) in soil and (II) under field conditions, yeast efficiency compared with mineral fertilizers in maize, therefore, two experiments were conducted. The first was conducted in controlled laboratory conditions in a completely randomized design in a 5 x 3 x 2 factorial, with three replications and 10 sampling periods. Therefore, experimental units 900 were installed to allow destructive sampling at the end of each period. The treatments consisted of four organic waste (EB, EG, ULCI and BS) and control (soil), three levels of soil moisture (15, 45 and 85% of maximum soil water holding capacity) and two conditions soil acidity improvement (uncorrected and corrected to reach a saturation basis of 70%). The kinetics of N release from the different nitrogen sources were determined by measuring ammonium and nitrate content periodically over 16 weeks. The organic N mineralization of waste fractions (FNmin) increased in the order: LISC (18-80%)> EG (27-70%)> EC (12-51%)> LE (5-26%). The increase of soil moisture improved the N mineralization in both limed soils as well as in the uncorrected for all wastes. The soil correction provided greater mineralization and nitrification in ...

O uso de resíduos orgânicos como adubo podem ocasionar melhorias nos atributos químicos e físicos do solo, uma vez que esses resíduos possuem quantidades significativas de nutrientes, principalmente N, e, altos teores de C orgânico. Em geral, a disponibilidade de N destes resíduos para o solo é menor quando comparada com fertilizantes sintéticos, devido à forma que o N se encontra ligado nesses adubos. Portanto, há necessidade de se fazer estudos que possam estimar a mineralização de N e o tempo de ocorrência dessas reações, auxiliando numa recomendação adequada desses resíduos como fertilizantes. Assim, objetivou-se com este trabalho avaliar (I) em condições de laboratório, mineralização de levedura seca inativa da cana-de-açúcar (LSIC), esterco de galinha (EG), esterco de bovino em confinamento curral (EB) e biossólido (BS) no solo e (II) em condições de campo, a eficiência da levedura em comparação com fertilizantes minerais na cultura do milho, para tanto, foram conduzidos dois experimentos. O primeiro foi realizado em condições controladas de laboratório com delineamento utilizado foi o inteiramente casualizado, em esquema fatorial 5 x 3 x 2, com três repetições e 10 períodos de amostragem. Portanto, foram instaladas 900 unidades experimentais para permitir amostragem destrutiva no final de cada período. Os tratamentos foram constituídos de quatro resíduos orgânicos (EB, EG, LSIC e BS) e controle (solo), três níveis de umidades do solo (15, 45 e 85% da máxima capacidade de retenção de água do solo) e duas condições de correção da acidez do solo (sem correção e corrigida para atingir uma saturação por bases de 70%). A cinética de liberação de N para as diferentes fontes de N foram determinadas medindo conteúdo de amônio e nitrato, periodicamente, ao longo de 16 semanas. As frações de mineralização do N orgânico dos resíduos (FNmin), foram maior na ...
Keywords: Milho - Cultivo; Levedos; Nitrogenio; Fertilizantes organicos; Colheita; Residuos organicos como fertilizantes; Organic wastes as fertilizer